Selective photodissociation of tailored molecular tags as a tool for quantum optics - Sezer, Ugur; Geyer, Philipp; Kriegleder, Moritz; Debiossac, Maxime; Shayeghi, Armin; Arndt, Markus; Felix, Lukas; Mayor, Marcel (Beilstein Journal of Nanotechnology, 2017)
Recent progress in synthetic chemistry and molecular quantum optics has enabled demonstrations of the quantum mechanical wave–particle duality for complex particles, with masses exceeding 10 kDa. Future experiments with even larger objects will require new optical preparation and manipulation methods that shall profit from the possibility to cleave a well-defined molecular tag from a larger parent molecule. Here we present the design and synthesis of two model compounds as well as evidence for the photoinduced beam depletion in high vacuum in one case.
Keywords: molecular quantum optics; photodepletion; photodissociation; synthetic photo-tags